Composite‐Structure Material Design for High‐Energy Lithium Storage. Issue 34 (3rd July 2018) - Wang, Lin; Shi, Ji‐Lei; Su, Heng; Li, Guangyin; Zubair, Muhammad; Guo, Yu‐Guo; Yu, Haijun
Abstract: High‐energy storage devices are in demand for the rapid development of modern society. Until now, many kinds of energy storage devices, such as lithium‐ion batteries (LIBs), sodium‐ion batteries (NIBs), and so on, have been developed in the past 30 years. However, most of the commercially exploited and studied active electrode materials of these energy storage devices possess a single phase with low reversible capacity or unsatisfied cycle stability. Continuous and extensive research efforts are made to develop alternative materials with a higher specific energy density and long cycle life by element doping or surface modification. A novel strategy of forming composite‐structure electrode materials by introducing structure units has attracted great attention in recent years. Herein, based on previous publications on these composite‐structure materials, some important scientific points focusing on the design of composite‐structure materials for better electrochemical performances reveal the distinction of composite structures based on average and local structure analysis methods, and an understanding of the relationship between these interior composite structures and their electrochemical performances is discussed thoroughly. The lithiation/delithiation mechanism and the remaining challenges and perspectives for composite‐structure electrode materials are also elaborated. Abstract : How to design, distinguish, and control the structure of composite‐structure electrode materials, and understanding their electrochemical charge/discharge reaction mechanism are elaborated in detail, providing a new direction for engineering high‐energy‐density active electrode materials. The remaining challenges are also discussed.